Integrated Diagenesis Study of Tight Gas Sandstone: The Permian Lower Shihezi Formation, Northern Ordos Basin, China - Qinghai Xu; Xiangyang Xie; Changmin Zhang; Lianfu Hai; Arthur Busbey (Lithosphere, 2022)
AbstractDiagenesis varies greatly from basin to basin and has been considered as the key control of the reservoir quality of tight sandstones. In this study, we analyzed the petrographic characteristics, diagenesis, and pore types and characteristics of the Permian Lower Shihezi Formation in the Ordos Basin. Results show that most of sandstones are litharenites with minor sublitharenites and feldspathic litharenites. The tight sandstones have ultralow permeabilities (averaging 0.67 mD) and porosities (averaging 8.35%), with pore-throat sizes ranging from 0.035 to 13.29 μm with 94.12% less than 5 μm. Overall, the tight sandstone reservoirs have undergone complex diagenetic alteration. Compaction and clay mineral cements are the two crucial diagenetic factors that controlled the tightness of the reservoirs. The compaction destroyed most of primary porosity, and the effective pores are mainly dissolved micropores, intragranular dissolved micropores, and micropores in clay minerals and mineral grains. The chlorite coating might have helped preserve a certain amount of porosity, but pore-lining chlorites significantly obstructed pore throats and reduced permeability. Results of the study provide insights and direct implications for the future success of exploration and production of the tight gas sandstone in the Ordos Basin and other similar tight sandstone reservoirs.